2014
DOI: 10.1002/2014je004704
|View full text |Cite
|
Sign up to set email alerts
|

The vertical distribution of Martian aerosol particle size

Abstract: Using approximately 410 limb-viewing observations from the Compact Reconnaissance Imaging Spectrometer for Mars (CRISM), we retrieve the vertical distribution of Martian dust and water ice aerosol particle sizes. We find that dust particles have an effective radius of 1.0 μm over much of the atmospheric column below 40 km throughout the Martian year. This includes the detached tropical dust layers detected in previous studies. Little to no variation with height is seen in dust particle size. Water ice clouds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 35 publications
9
54
0
Order By: Relevance
“…In this work, we present the seasonal evolution and variability of the vertical distribution of Martian water ice cloud particle size (specifically, effective radius [r eff ]) as observed by the Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) in limb‐scanning mode. This work extends the analysis presented by Guzewich et al (). These observations represent an important metric to evaluate the performance of Mars GCM microphysical modules and guide their improvement while also providing a window into Martian atmospheric aerosol interactions and processes.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this work, we present the seasonal evolution and variability of the vertical distribution of Martian water ice cloud particle size (specifically, effective radius [r eff ]) as observed by the Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) in limb‐scanning mode. This work extends the analysis presented by Guzewich et al (). These observations represent an important metric to evaluate the performance of Mars GCM microphysical modules and guide their improvement while also providing a window into Martian atmospheric aerosol interactions and processes.…”
Section: Introductionsupporting
confidence: 89%
“…The seasonal evolution of water ice cloud particle size in the polar regions (50–90° in each hemisphere) is more complicated. Guzewich et al () found that the polar hood clouds had roughly uniform particle sizes of 1.5 μm. Our more complete seasonal record shows that the end of the polar hood cloud season in the northern hemisphere (L s = 330–30°) does indeed exhibit fairly uniform ice particle size with altitude near 1.5 μm, but the remainder of the observable year exhibits different behavior.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the observations of “detached dust layers” observed by MCS [ Heavens et al ., ] and TES [cf. Guzewich et al ., ], which represent an elevated maximum in the dust profile at this altitude. The concentrations of dust aerosols of size 3 µm are nearly zero at all altitudes during the dust storms.…”
Section: Resultsmentioning
confidence: 99%
“…Heavens et al ., ; cf. Guzewich et al ., ]. The dust profiles are calculated from the following equation n(),rz~k0.1em·0.1emns0.1em·0.1emn()r0.1em·0.1emA0.12em()z where n ( r ) is the density distribution of aerosol particles of radius r , n s is observed dust concentration at the surface of Mars, the constant k=1true/()0nrdr is obtained by integrating n ( r ) from r to r + d r , and A ( z ) is a parameterized scheme at altitude z as given below: A()z=[]1normalexp[]prefix−()znormalFnormalH2FL2+B0.1em·0.1emnormalexp[]prefix−()znormalPnormalH2PT2 …”
Section: Seasonal and Vertical Variability Of Dustmentioning
confidence: 99%
“…The global nature of this phenomenon and the clear global solsticial pause at L s = 90-110° suggests that the mechanism suppressing dust lifting near solstice is not relegated to the winter polar region, nor is it solely related to the weakened eddy activity near winter solstice. Given that 1-1.5 µm dust particles [Guzewich et al, 2014] settle out of the atmosphere on timescales of days to weeks [Pollack et al, 1979;Kahre et al, 2008], the previously identified pause in storm-scale lifting during these time periods should have a noticeable effect on the global dust opacity unless the majority of lifting occurs at significantly different times or scales.…”
Section: Dust Storm Climatologymentioning
confidence: 99%